Pengaruh Pemanfaatan Sistem Informasi Keuangan Daerah dan Pemahaman Standar Akuntansi Pemerintah Terhadap Sistem Pengendalian Laporan Keuangan - Nasution, Nazariah; Prayoga, Yudi; Siregar, Marlina (Jurnal Manajemen Akuntansi (JUMSI), 2025)
This research is grouped on associative quantitative methods that are characterized by asking the relationship between two or more variables ( Sugiono 2019 : 65 ) to determine the effect of the relationship of the independent variable with the dependent variable.  With a sample of 90 respondents, as known as variable X1 is the utilization of regional financial information systems, variable X2 is the understanding of regional accounting standards and variable Y is the financial statement control system. Stated, Based on research that obtained Fhitung value of 26.811 is greater than 2.71 and sig. 0.000 < 0.05 indicates that the utilization of the regional financial information system (X1) and understanding of Government Accounting Standards (X2) simultaneously have a positive and significant effect on the financial statement control system (Y).  And found that the value of R Square (R2) of 0.367. Which means that the financial statement control system can be explained by the variable utilization of regional financial information systems and understanding of government accounting standards by 36.7%, while the remaining 63.3% are influenced by other factors not examined in this study.